I need to solve for y with this equation, but I'm not sure how to get started.

(y + 4)^2 = 2y^2 + 9 + 14

Now

2y^2 - y^2 - 8y + 9 + 14 - 16 = 0

y^2 - 8y + 9 - 2 = 0

y^2 - 8y + 7 = 0

y^2 - y - 7y + 7 = 0

y(y - 1) - 7(y - 1) = 0

(y - 1)(y - 7 )= 0

y - 1 = 0 , y - 7 = 0

y = 1 , y = 7

Hence y = 1 , 7

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up